Analysis of the influence of chlorides in the mechanical behaviour of high-performance steel fibre reinforced cementitious composites - de Melo Vieira, Mylene (2021)
Steel fibres are used in high amounts in high-performance steel fibre reinforced cementitious composite (HPSFRCCs) and ultra-high-performance steel fibre reinforced cementitious composite (UHPSFRCCs) to enhance its structural performance. Due to the amount and randomly distribution of steel fibres in the cementitious matrix a level of damage in the aesthetic and mechanical response of fibres may be expected for structures under chloride exposition. This work aims to assess the structural behaviour of uncracked HPSFRCCs subjected to chlorides. Eight mixes of HPSFRCCs with different fibre content (40, 80, 120 and 160 kg/m3), with and without chlorides added to the mixes were designed. Prismatic specimens were cast and exposed to two curing conditions: initially in wet room and then in climatic room. The mechanical properties were obtained by means of the 3-point bending tests. The presence of corrosion in cross-section of the specimens were also analysed after mechanical tests by means of visual inspection. The results showed that the chloride added to the mixes has little influence on the post-cracking response of fibres.